Beyond Black-Letter Antitrust: Pharmaceutical Patent Expiry, GenericCompetition, and the Rule of Reason in the Pfizer-Dexa Amlodipine Case a Comparative Legal-Systemic Study of Indonesia, the United States, the European Union, and Japan - Raymond R. Tjandrawinata (Asian Journal of Social and Humanities, 2026)
This article examines the Pfizer-Dexa amlodipine case as a critical point of intersection among pharmaceutical patent law, generic competition, market regulation, and antitrust adjudication. Rather than treating the case merely as a failed cartel prosecution, the article argues that it reveals a deeper methodological problem in pharmaceutical competition law: the risk of interpreting high prices and parallel market behavior as evidence of collusion without conducting a sufficiently systemic economic and legal inquiry. Using Indonesia as the primary case study and comparing it with the United States, the European Union, and Japan, the article develops the concept of a pharmaceutical systemic rule of reason. This framework requires competition authorities and courts to assess patent expiry, drug approval, generic entry, branded generics, prescription dynamics, distribution structures, and patient access as interconnected components of a regulated health market. The article contributes to antitrust theory by demonstrating that pharmaceutical competition cannot be reduced either to patent absolutism or anti-cartel formalism. Instead, it must be evaluated as a living system in which innovation, access, evidentiary rigor, and market fairness are held together.